Qualidade de sementes de soja em função da variabilidade do solo - Müller, Danielle Helena (2016)
This study aimed to verify the quality of soybean seeds as a function of soil variability in a production field. The experimental data were collected at 138 points georeferenced in producing soybean property located in Santo Antônio de Leverger - MT. The soil collection for chemical, physical and microbiological was held in November 2013 and the collection of soybean cultivar TMG 1179 was held in January 2014, a soil containing production field with texture gradient. On the ground we evaluated the levels of macronutrients (phosphorus, potassium, calcium and magnesium), pH, organic matter (OM), cation exchange capacity (CEC) and base saturation (V%), grain size, density, porosity , humidity and population of nematodes and mycorrhizal fungi. For the seed was evaluated productivity, mass of 1000 seeds, size, health and physiological potential through germination, emergency beds, electrical conductivity, accelerated aging and tetrazolium. Data were submitted to descriptive analysis, correlation and geostatistics and the parameters set semivariograms were used for preparation of spatial distribution maps of the variables analyzed. There is no direct correlation between the quality of soya beans produced and attributes evaluated in the soil. There spatial variability of the attributes evaluated in the seeds and in the soil, indicating that the area for the production of soybean seeds can be divided into management areas, which allows the definition of areas to be collected and disposed in a seed production field.